Distribution Mapping and ex-situ Conservation of Hildegardia populifolia (DC.) Schott & Endl.: A Critically Endangered and Multipurpose Tree Species - Priyanka,; Panwar, Giriraj Singh; Chauhan, Sandeep Kumar (Indian Forester, 2025)
Hildegardia populifolia is a critically endangered tree species of the peninsular India. Fragmented populations of the species are distributed in India and Indonesia. It is being used by the local people for its medicinal and other economical purposes. The overexploitation of species from wild and fragmentation of small population has rendered the species towards extinction risk. Thus, the present study was aimed with the distribution mapping and ex-situ conservation of species for the preservation of germplasm.